2021
DOI: 10.1542/peds.2021-052106
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating to Advocate in Primary Care for Children During COVID-19

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…All but two of the 71 publications indicated that the professional society listserv had been used merely to distribute surveys, to recruit participants to studies, and to solicit data for studies. One publication 8 reported use of a professional listserv to discuss care, to organize webinars, to provide updates on local and national data, and to plan next steps in pediatric care during the pandemic. Another publication, 9 a letter to the editor, reported creation of an informal listserv to share opinions, practices, and procedures about autopsies on COVID decedents.…”
Section: Resultsmentioning
confidence: 99%
“…All but two of the 71 publications indicated that the professional society listserv had been used merely to distribute surveys, to recruit participants to studies, and to solicit data for studies. One publication 8 reported use of a professional listserv to discuss care, to organize webinars, to provide updates on local and national data, and to plan next steps in pediatric care during the pandemic. Another publication, 9 a letter to the editor, reported creation of an informal listserv to share opinions, practices, and procedures about autopsies on COVID decedents.…”
Section: Resultsmentioning
confidence: 99%
“…The role of pediatrician advocacy has been highlighted in numerous communities throughout the United States where collaboration with data collection and sharing, testing, treatment, and policy have been prioritized. 90 , 91 , 92 Exemplar communities have established pediatric collaboratives, with subsequent creation of listservs, accumulation of robust data sets, and crafting of local protocols designed to help inform local best practices and ultimately aid school groups in decision-making regarding safe school protocols. 90 Pediatricians have established learning networks across sectors and have built community partnerships with infrastructure designed to outlast the COVID-19 pandemic and ideally address public health needs in the years to come.…”
Section: Advocacymentioning
confidence: 99%